DOES MANAGERIAL OPPORTUNISM EXPLAIN THE DIFFERENTIAL PRICING OF LEVEL 3 FAIR VALUE ESTIMATES?. (5th June 2018) - Robinson, Dahlia; Smith, Thomas; Valencia, Adrian
Abstract: Using hand‐collected Level 3 data, we find that banks near key capital ratios report higher unrealized gains in Level 3 assets, consistent with managers using Level 3 valuations to boost capital ratios. Additionally, we document an incremental pricing discount for Level 3 assets among these firms, suggesting that the pricing discount observed by prior research may not be entirely due to measurement error inherent in Level 3. Furthermore, we observe that this opportunistic behavior diminishes under the new Financial Accounting Standards Board disclosure regime, suggesting that the expanded disclosures may increase the value relevance and reliability of fair value measurements.